Development of video learning media assisted by Sparkol Videoscribe to facilitate the ability to understand mathematical concepts of students - Diki Wahyudi; Zubaidah Amir MZ (SAINTIS Publishing, 2022)
This study aimed to develop and produce video learning media assisted by Sparkol Videoscribe that are valid, practical, and able to facilitate understanding of mathematical concepts. This type of research is development research using the ADDIE model which includes five steps, namely: analysis, design, development, implementation, and evaluation (evaluation).This study was conducted at the Junior High School (SMP) Islam Terpadu Abdurrab Pekanbaru. The subjects of this study are learning materials experts and educational technology experts, as well as VIII grade students of Junior High School (SMP) Islam Terpadu Abdurrab Pekanbaru and the object of this study is video learning media assisted by Sparkol Videoscribe. Data collection techniques include questionnaires and concept understanding ability tests. The data analysis technique used is the descriptive data analysis technique. Based on the results of validation by a team of validators consisting of 2 learning material experts and 3 Education technology experts. The validation results from the learning material expert validators show that the resulting learning videos have very valid criteria with a percentage level of validity of 98%, and the assessment of educational technology experts has very valid criteria with a validity percentage of 84%. Then the results of the practicality test that was tested on VIII grade students of SMP Islam Terpadu Abdurrab were grouped into two groups, namely a small group with a total of 8 students respondents obtaining a score of 86.9% with a very practical category, and a limited group with a total of 34 students receiving a score of 85, 73% with very practical category. Furthermore, from the posttest results, the male class got an average score of 86.38% with high criteria, and the female class got a score of 90.5% with high criteria. Next, a t-test was conducted on the posttest results for male and female classes, with the results tcount (-1.444) ttable(1.694), with the conclusion that there was no significant difference between male and female classes.